Heavy Metal Ion Stress on Halobacterium salinarum R1 Planktonic Cells and Biofilms - Völkel, Sabrina; Fröls, Sabrina; Pfeifer, Felicitas (Frontiers in Microbiology, 2018)
Halobacterium salinarum R1 is an extremely halophilic archaeon, able to attach to the surface and to form characteristic biofilm structures under physiological conditions. However, the effect of environmental stress factors like heavy metals on biofilms was still unknown. Here, we report on the first insights into Halobacterium salinarum biofilm formation when exposed to copper, nickel and zinc and describe the effects of metal ions on the architecture of mature biofilms. We also studied the effects on gene expression in planktonic cells. Investigation of planktonic growth and cell adhesion in the presence of sub-lethal metal concentrations yielded an up to 60% reduced adhesion in case of copper and a significantly enhanced adhesion in case of zinc, whereas nickel treatment had no effect on adhesion. A PMA-qPCR assay was developed to quantify live/dead cells in planktonic cultures and mature biofilms, enabling the investigation of cell vitality after metal exposure. An increased resistance was observed in biofilms with up to 80% in case of copper- and up to 50% in case of zinc exposure compared to planktonic cells. However, nickel-treated biofilms showed no significant increase of cell survival. Microscopic investigation of the architecture of mature biofilms exposed to lethal metal concentrations demonstrated an increased detachment and the formation of large microcolonies after copper treatment, whereas the number of adherent cells increased strongly in nickel-exposed biofilms. In contrast, zinc exposed-biofilms showed no differences compared to the control. Analysis of the expression of genes encoding putative metal transporters by qRT-PCR revealed specific changes upon treatment of the cells with heavy metals. Our results demonstrate diverse effects of heavy metal ions on Halobacterium salinarum and imply a metal-specific protective response of cells in biofilms.